Implikasi Progresivisme dalam Pembelajaran: Membangun Siswa yang Aktif dan Inovatif - Siti Anisa Al Maulani; Abdul Khobir; Seviani Najiyah; Muhammad Zufar Sabiq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The implications of progressivism in learning serve as an essential foundation for building an educational process that fosters active, creative, adaptive, and innovative students in accordance with 21st-century competency demands. The progressive approach positions students at the center of the learning process through direct experience, deep exploration, collaboration, dialogue, experimentation, and problem-solving relevant to real-life contexts, ensuring that learning is not only focused on content mastery but also on the development of potential, character, independence, and higher-order thinking skills. This study employs a literature review method by examining primary and secondary sources on the principles of progressivism, active learning strategies, and their relation to the Merdeka Curriculum as a foundation for national educational transformation. The findings indicate that progressivism plays a significant role in shaping critical thinking, creativity, communication, collaboration, digital literacy, and initiative through the implementation of learning by doing, project-based learning, simulations, scientific experiments, reflective discussions, and technology integration that strengthens learner autonomy. This experience-based approach effectively supports students in constructing knowledge independently while enhancing confidence, responsibility, social awareness, and cooperative skills. However, its implementation still faces challenges such as passive learning culture, limited teacher competence in active methods, insufficient facilities, overloaded curriculum, psychosocial barriers, academic anxiety, and students’ low confidence in expressing opinions. These findings affirm that progressivism is highly relevant to educational reform in Indonesia; therefore, improving teacher competence, strengthening facilities, reinforcing policies, providing continuous support, and creating safe, democratic, inclusive, and supportive learning environments are essential to help students develop optimally as independent, creative, and innovative learners.